Gender politics and everyday life in state socialist Eastern and Central Europe (Basingstoke, 2010)
"Did socialism liberate women? Twenty years after the collapse of communism in Eastern Europe, this collection of essays from European and North American scholars examines socialist policies and women's everyday lives to demonstrate that this question cannot be answered with an emphatic 'no,' but has multiple answers that require attending to many voices and stories. Focusing on a range of issues - such as worker identity, marital and family relations, consumer culture, leisure, sexuality, reproduction, activism, and resistance - Gender Politics and Everyday Life reveals that women experienced socialism in diverse, ambiguous, and in some cases empowering ways. These nuanced and multidisciplinary investigations provide new depth to the study of state policy, gender relations, and women's and men's lives, illustrating that there is no simple, coherent narrative of life under state socialism, but rather multiple, competing, and often contradictory ones."